Analysis of coping styles of elderly women patients with stress urinary incontinence - Binbin Yu; Hongmei Xu; Xiaolin Chen; Li Liu (International Journal of Nursing Sciences, 2016)
Objective: The aim of this study was to survey the coping style and related factors of elderly women with stress urinary incontinence (SUI) and provide a strong theoretical basis for promoting a positive coping style to improve quality of life in these patients. Methods: Cross-sectional surveys addressing SUI cognition and coping techniques of 520 elderly women patients with SUI were administered between July 2013 and February 2014. Results: Elderly women with SUI had significantly higher avoidance and acceptance-resignation scores than the normal population (p < 0.05). Age, marital status, education level and stress urinary incontinence cognitive level all influenced the medical coping style of these patients. Conclusions: Elderly female patients with SUI differ in the factors that influence their coping styles; therefore, clinical and community medical staff should include a comprehensive analysis that takes these factors into consideration when working with patients with SUI to guide them in adopting a positive coping style.